PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN IKA SMPN 2 BANDUNG - Terawati, Mira Teram; Rachman, Fatwa Rubiar; Astuti Dinah, Resta Puji (Jurnal Abdi Citra, 2024)
This Community Service (PKM) Activity by the Academy of Accounting Bandung (A2B) is one of the manifestations of the Tri Dharma of Higher Education, which is to provide benefits to the community. This PKM activity is intended for the management of IKA SMPN 2 Bandung located on Jl. Sumatera No. 42 Bandung. The method of implementing PKM activities is carried out by providing assistance in the preparation of financial statements using exel software. This PKM consists of several stages, namely preparation and interview, discussion and introduction of programs, signing agreements, assistance in preparing financial statements, as well as evaluation and follow-up. The output resulting from this community service activity is the excel application of financial statements of IKA SMPN 2 Bandung.